2018
DOI: 10.1016/j.ijbiomac.2017.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Anion–π interactions in active centers of superoxide dismutases

Abstract: We investigated 1060 possible anion-π interactions in a data set of 41 superoxide dismutase active centers. Our observations indicate that majority of the aromatic residues are capable to form anion-π interactions, mainly by long-range contacts, and that there is preference of Trp over other aromatic residues in these interactions. Furthermore, 68% of total predicted interactions in the dataset are multiple anion-π interactions. Anion-π interactions are distance and orientation dependent. We analyzed the energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…The repulsive nature of those interactions emerges from the unfavorable geometries of interacting pairs in the crystal structures and usually is counterbalanced by other interactions. Namely, when examined under isolated conditions, this type of interaction is considered unfavorable, but similar to other potentially unfavorable interactions, their influence can be compensated by other interactions from the rest of the polypeptide chain . This observation indicates that hydrogen bonding free energy is important for maintaining the stability of phycocyanin proteins.…”
Section: Resultsmentioning
confidence: 96%
“…The repulsive nature of those interactions emerges from the unfavorable geometries of interacting pairs in the crystal structures and usually is counterbalanced by other interactions. Namely, when examined under isolated conditions, this type of interaction is considered unfavorable, but similar to other potentially unfavorable interactions, their influence can be compensated by other interactions from the rest of the polypeptide chain . This observation indicates that hydrogen bonding free energy is important for maintaining the stability of phycocyanin proteins.…”
Section: Resultsmentioning
confidence: 96%
“…Earlier publications confirmed π interactions as long-range interactions, having notable binding forces even at intermolecular distances of 7 Å. [27][28][29] Fig. 1.…”
Section: Amide- Interaction Analysismentioning
confidence: 76%
“…calculations were performed on structurally reduced model systems. 29 We used formamide (1) as mimics for amide groups. Phenylalanine was simplified to methylbenzene (2), histidine to 5-methyl-1H-imidazole (3), while tryptophan and tyrosine were reduced to 3-methyl-1H--indole ( 4) and 4-methyphenol (5), respectively (Fig.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, the water molecule had two short contacts to hydrogen‐bond acceptors, and the authors concluded by inference that one of the lone‐pairs of the water molecule must be oriented along a normal to the indole plane. Since then, such interactions, baptized “lone‐pair–π (lp–π) interactions”, became widely recognized as a force stabilizing biomolecules …”
Section: Introductionmentioning
confidence: 99%